2010
DOI: 10.1016/j.neuroscience.2010.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of Nogo/Rtn4 ameliorates behavioral and neuropathological outcomes in amyloid precursor protein transgenic mice

Abstract: The cognitive impairment in Alzheimer's disease (AD) is associated with synaptic loss, neuritic sprouting and altered neuroplasticity. Compensatory neuritic sprouting might be beneficial, while aberrant sprouting could contribute to the neurodegenerative process. Nogo (or Rtn4) is a major myelin-derived inhibitor of axonal sprouting in adult CNS. Recent evidence has implicated both the Reticulon family of proteins and a receptor for Nogo, NgR, in reducing amyloid-β production, a key step in AD pathogenesis. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Among them, expression levels of 8 genes ( ATXN10 , DCC , KIF3A , MAP1B , PAK3 , PFN2 , RTN4, UCHL1 ) were also significantly decreased in AD hippocampi (GEO DataSets GSE36980)6. Downregulation of MAP1B and UCHL1 in the AD brain have been shown previously3738, and moreover, PAK33940 and RTN44142 were known to be associated with AD pathology. Taken together, the PS1 P117L AD neurons reproduce major characteristics observed in neurons in AD brain, and are useful for understanding molecular mechanisms of AD pathology in neurons.…”
Section: Discussionmentioning
confidence: 91%
“…Among them, expression levels of 8 genes ( ATXN10 , DCC , KIF3A , MAP1B , PAK3 , PFN2 , RTN4, UCHL1 ) were also significantly decreased in AD hippocampi (GEO DataSets GSE36980)6. Downregulation of MAP1B and UCHL1 in the AD brain have been shown previously3738, and moreover, PAK33940 and RTN44142 were known to be associated with AD pathology. Taken together, the PS1 P117L AD neurons reproduce major characteristics observed in neurons in AD brain, and are useful for understanding molecular mechanisms of AD pathology in neurons.…”
Section: Discussionmentioning
confidence: 91%
“…unpublished results). In this respect, the single genetic ablation of MAIs [75] alone or with semaphorin receptors [76] is not strong enough to support axon regrowth after SCI. In contrast, it seems that blocking the MAI receptors NgR1 and NgR3 and CSPG receptors yields better results [71].…”
Section: Discussionmentioning
confidence: 99%
“…GAP-43 plays a key role in guiding the growth of axons and modulating new connections and enables neurons to sprout new terminals (Aigner et al, 1995). Recent studies demonstrated that decrease in Nogo-A resulted in an increase in axonal plasticity as determined by GAP-43 expression (Dietrich et al, 2005; Masliah et al, 2010). Increased expression of GAP-43 was also observed in the fimbria in prenatal cocaine treated animals (Clarke et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine administration also produces an increase in extracellular dopamine levels, and changes in WM pathology have been observed in areas away from cc (Hermida-Ameijeiras et al, 2004; Masliah et al, 2010). Oligodendrocytes express D2 and D3 receptors for dopamine, and stimulation of these receptors resulted in decreased transition of immature oligodendrocytes to mature oligodendrocytes (Bongarzone et al, 1998).…”
Section: Discussionmentioning
confidence: 99%